TEACHING CHEMICAL PROBLEM SOLVING AND CLASSIFICATION AS A PEDAGOGICAL PROBLEM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article describes the problems that arise when solving chemistry problems in general secondary schools.